Comparative Study on the Malaysian Sustainable Building Assessment Tools - Usman, Abdullahi Mohammed; Abdullah, Mohammad Kamil (International Journal of Integrated Engineering, 2018)
Green Building Index (GBI) and Green Real Estate (GreenRE) are the two existing green building assessment tools specifically design and developed for Malaysian tropical weather, environmental and development context, cultural and social needs. GBI developed 15 assessment tools and GreenRE have 4 assessment tools therefore, only four assessment tools were compared. The total credits allocation are 100/154Cr, 100/183Cr and 100/184Cr and total parameters of 39Pr/24Pr, 51Pr/29Pr and 44Pr/30Pr for RNB, NRNB, NREB assessment tools for GBI/GreenRE respectively. Among the criteria, energy, water, indoor and outdoor environmental qualities were given high priority with high credit and parameters allocation. GreenRE give more priority in EEF and WEF category as compared to GBI with putting more priority over GreenRE in the remaining as it consider more categories of buildings, parameters in the remaining criteria and higher rating grade. It is easier to score credits and attain high ratings in the GreenRE assessment tools than GBI assessment tools even though in both the sustainability issues considered are similar. The results from GBI and GreenRE assessment exercise are solely dependent on the personality, quality and experience of the assessor. All the tools developed by GreenRE and GBI are pointing to a single similar objective that is the implementing the principle of sustainability in the Malaysian build environment and hence they are both suitable for assessing Malaysian building.